What Anchors the Tu Do? - Byrne, Denis (Journal of Contemporary Archaeology, 2017)
A 1970s Vietnamese refugee boat, the Tu Do, exhibited at a maritime museum in Sydney, commemorates Australia’s decision to open its borders to those fleeing the aftermath of the Vietnam War. What concerns me is the absence in the museum’s interpretive material of any reference to the contemporary interdiction at sea of asylum seekers attempting to reach Australia. This means the Tu Do is discursively quarantined from its companion objects, those hundreds of refugee boats turned back from Australia’s border in recent years. In asking ‘What anchors the Tu Do?’, in asking what prevents it drifting on a current of similitude to those other boats, I bring into question the whole field of migration heritage as it is practiced in Australia and beyond. Immured as this field is in methodological nationalism, it seems not to be far-fetched to suggest that heritage practice be considered alongside other practices of border maintenance.